2011
DOI: 10.4025/actasciagron.v33i4.4611
|View full text |Cite
|
Sign up to set email alerts
|

The germination of bush mint (Hyptis marrubioides EPL.) seeds as a function of harvest stage, light, temperature and duration of storage

Abstract: ABSTRACT. This study evaluated the effect of light, temperature, physiologic stage at harvest and length of time on the germination of Hyptis marrubioides seeds. Two trials were conducted. The first experiment was performed immediately after the seed harvest and consisted of a 2 x 3 x 3 factorial design with 2 environmental conditions (light and dark), 3 temperatures (20, 30 and 20/30ºC) and 3 seed harvest times (green colored seeds, light brown seeds and dark brown seeds). The second experiment was conducted … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
2
0

Year Published

2016
2016
2022
2022

Publication Types

Select...
3
1

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(3 citation statements)
references
References 11 publications
1
2
0
Order By: Relevance
“…The requirement for seeds germination of different species at alternate temperatures was also verified by some authors such as Sales et al (2011) who stated that germination increased at constant temperatures of 30 °C and alternated at 20-30 °C in all light regimes and for seeds of Crataeva tapia. Galindo et al (2012), found only the alternating temperature of 20-30 ºC under the regimes of white and red light.…”
Section: Germination In Different Light Qualitiessupporting
confidence: 54%
“…The requirement for seeds germination of different species at alternate temperatures was also verified by some authors such as Sales et al (2011) who stated that germination increased at constant temperatures of 30 °C and alternated at 20-30 °C in all light regimes and for seeds of Crataeva tapia. Galindo et al (2012), found only the alternating temperature of 20-30 ºC under the regimes of white and red light.…”
Section: Germination In Different Light Qualitiessupporting
confidence: 54%
“…Regardless of the product used for the treatment and of cultivars, seed germination was reduced in the treated and stored and the smallest seedlings were obtained when the seeds quality after storage were assessed. This reduction in germination of seeds is due to many circumstances such as the environmental conditions during the production of seeds, insect attack, lipid and water content in seeds, presence of mechanical damage arising from transport and processing, storage conditions, and especially, in the case of seed with high quality, of the chemicals used in seed treatment (Sales et al, 2011). In this study, when the seeds were stored there was phytotoxic effect treated by the contact time of the products with the seeds.…”
Section: Resultsmentioning
confidence: 99%
“…Reductions in seed germination levels were related to the production environment and storage conditions and duration. Other negative factors were mechanical damages caused during the harvest-threshing and seed cleaning processes, as well as the seed fungi load and chemicals used for the seed treatment [29,30]. Seedlings wilting was also observed during the germination test due to soil infestation and seed contamination by fungi.…”
Section: Qualified Seedmentioning
confidence: 99%